The value of information in municipalities: A South African case study in the Eastern Cape - Forlee, Bianca (Department of Information Systems, 2022)
Within the South African context, there is clear legislation and policy advocacy on the importance of community participation in facilitating inclusive decision-making. Statutory frameworks require municipalities to inform citizens of their rights and encourage them to contribute to municipal initiatives. Public participation and access to information are critical elements of good governance. However, implementing the policies is not always executed as intended. This can be attributed to various reasons such as the lack of resources, institutional capacity, poor administration of government resources and redressing historical backlogs of service delivery. Research also suggests that citizens feel excluded from the decision-making processes as they lack access to information to participate constructively. Governance has become a popular concept in literature, especially where the focus is on reducing inequality, reducing poverty and promoting sustainable development in developing countries, and consequently considers the relationships between government and civil society. The intention of “good governance” is to strengthen accountability and responsiveness of policies and strategies by enabling communities to engage and have an influential voice, especially on decisions that affect their livelihood. This research aims to examine how information sharing practices between municipalities and communities affect good governance. One theme that consistently emerges in the review of the legislation and policy documents is citizenry's inclusion in the municipal decision-making process. Public participation has an influential role in good governance. However, there is a gap in the importance of information sharing and how to share this information to facilitate effective public participation. Thus, this study integrated the principles of good governance and Information Value Chain to determine how municipalities use and disseminate information to their communities and use citizen knowledge to improve good governance. The study included reviewing various policy documents and literature, semi-structured interviews with municipal staff and focus groups with community members, follow-up meetings, workshops, and observations. By combining the Theory of the Information Value Chain with the Good governance Principles Framework, data could be analysed by categorising data into themes.